Pendidikan Keluarga dan Perkembangan Kemandirian Anak dan Remaja - Khotijah Khotijah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2015)
The family is the first and primary education for children. Parents have the most decisive role of family atmosphere. The way of Parenting and the atmosphere will influence the children’s attitude and personality and it will also decide whether or not the children get their success in the future. The children’s self-reliance is one of the important things to decide their success , their parents’ and nations’s sucscess in the future. Therefore, parents should educate, train, and guide their children. Beside that, they have to be models for their children from an early age in order they become a confident figure and have high self-reliance. If the children have high self-reliance nature, they will not always depend on other parties, then they will be confident, strong and not easily discouraged. Adolescence is a vulnerable period for every child. At this time, parents should be able to create a communicative atmoshphere and harmonious family, so the child will be always extrovert with family members, especially to the parents. It is intended that adolescents will not find more attention from other outside without their parent consent. Harmony doesn’t mean as living without any problems, but it is how to overcome and resolve the problems. It is now known that the attention is absolutely necessary because there are many factors that influence the development of children as a friend and the electronic media that sometimes display a variety of phenomena that are not in accordance with the purpose of forming attitudes of children and adolescents. The role of parents is needed in educating and guiding children and teens. They also should be active in a variety of roles in monitoring and assisting them.